Role of Ayurveda Modalities in the Management of Urdhwag Amlapitta (Gastro Esophageal Reflux Disease): A Critical Review (AYUSHDHARA, 2023)
For long time various types of communicable diseases were biggest killer diseases globally. But now a days trend become changing towards increased prevalence of chronic diseases due to changing their diet pattern, lifestyle and behavioral pattern. In these chronic diseases Gastro Esophageal Reflux Disease (GERD) is the Gastro-intestinal disorder defined by recurrent troublesome heart-burn and regurgitation. Patient with GERD can be medicated empirically with Antacids and proton pump Inhibitor’s but in most of the cases patient do not respond to such treatment absolutely and several adverse effects arises after prolonged use. Ayurvedic texts classifies the broad spectrum of Amlapitta into Urdhwag and Adhog Amlapitta in which GERD shows similarity with Urdhwag Amlapitta on the basis of causes and symptoms. Aim and Objectives: The current review article illustrates the mode of action of Ayurvedic procedures (Shodhana Chikitsa) and formulations (Shamana Chikitsa) which is safe and effective for GERD (Urdhwag Amlapitta) Material and Methods: Ayurvedic texts referred are Charak Samhita, Yog Ratnakar, Bhaisjya ratnavali and contemporary modern texts and published manuscripts. Discussion: Detailed protocol treatment for Amlapitta in the form of Shodhana and Shamana Chikitsa discussed in terms of drugs and diet, should be applied considering the association of Dosha. Conclusion:  This review article will helpful to Ayurveda scholars, academicians, clinicians and researchers for the future prospect to plan the research work on same topics.